A mixed-longitudinal study of children's growth, motor development and cognition. Design, methods and baseline results on sex-differences - Ana Carolina Reyes; Raquel Chaves; Adam D. G. Baxter-Jones; Olga Vasconcelos; Go Tani; José Maia (Taylor & Francis Group, 2018)
Background: There is a renewed interest in longitudinal studies which link children's growth, motor and cognition development. This is important for both educational outcomes and identification of children who are at risk. Aim: To identify cross-sectional sex-differences. Subjects and methods: In total, 1166 Portuguese children, aged 4-11 years, were recruited into the Growth, Motor Development and Cognition Study (GMDC-Vouzela study). Measures included: anthropometry, gestational development, motor coordination, cognitive performance, laterality, physical fitness, metabolic syndrome risk, lifestyle characteristics and environmental exposures. Analysis of covariance was used to compare outcomes between boys and girls, adjusting for chronological age. Results: Most variables did not show significant differences between the sexes (p > 0.05). However, girls had more body fat mass than boys (p < 0.05) and boys were significantly heavier at birth (p < 0.05); furthermore, boys outperformed girls in a hopping high coordination test (p < 0.001) and were more physically fit (p < 0.05). Conclusions: Baseline results from the GMDC-Vouzela study indicate the dynamic relationships between children's biological and environmental characteristics. They also highlight lifestyle traits that will most likely effect subsequent growth, motor and cognitive development.